ANIMA DAN TRANSFORMASI NILAI KARAKTER: STUDI KASUS PENGARUH FIGUR FEMININ TERHADAP KEPRIBADIAN LINTANG DALAM NOVEL ‘PULANG’ - Laras Fitria; Jeffry Handhika; Dwi Rosita Sari (CV Edujavare Publishing, 2026)
The archetype of the anima, as a representation of the feminine unconscious in the male psyche, plays a significant role in personality integration and character transformation. This research aims to describe the dynamics of the anima archetype and its influence on the transformation of the main character's character values in the novel Pulang by Leila S. Chudori. This study uses a qualitative approach with a case study design, focusing on the character Lintang as the research subject. Data was collected through structural analysis of the text to identify anima projections in female figures (Surti, Alam, and Tanya) and their interactions with Lintang. Data analysis was carried out thematically through the process of reduction, presentation, and interpretation of meaning based on Carl Gustav Jung's psychoanalytic theory. The findings show that female figures function as anima manifestations that guide Lintang through the process of confronting his shadow, reconciling with his traumatic past, and ultimately achieving self-integration (individuation). The anima facilitates the transformation of Lintang's character values from being rigid, fugitive, and full of resentment to becoming more empathetic, forgiving, responsible, and finding his true identity. This research confirms that literary works can be a psychological case study that illustrates the process of character development through archetypal dynamics.